Infective keratitis: a concise overview of the clinical characteristics and treatment of keratitis caused by microbial agents - Chandra, Mahesh; Singh, Jitendra; Jha, Ayush (International Journal Of Community Medicine And Public Health, 2024)
The following document provides an overview of microbial keratitis, a well-known sight-threatening inflammation of the cornea that progresses to the corneal ulcer. Sometimes, such infection is difficult to identify and cure due to the involvement of multiple pathogens implicated in the specific disorders because of similar symptoms and immunological responses. Instead of fungi and protozoa, viruses and bacteria are the most prevalent pathogens that cause microbial keratitis. A virus contains protein-encased genetic material and may infect any living creature, including bacteria and fungi, by replicating inside the host's cell and infecting neighbouring cells. Bacteria are complicated pathogens that may thrive in any media and cause harm to host cells, often through the production of toxins. Fungi are far more difficult; they spread quickly and can cause harm to several organs at the same time if the immune system is compromised. Protozas are found freely in the environment and once invade the cornea, divide quickly and become difficult to identify as well as treat, because of their involvement or in conjunction with polymicrobials. These microbes show common symptoms after invading the cornea although; their common diagnostic procedures show different results to trace out their existence in the tissue. Up to some extent, specific treatment can cure the disease with certain conditions according to a load of microbes, therefore visual status gets hampered, otherwise total loss of the eye takes place due to the endophthalmitis.